Barmerovnene: Pottemagerovne fra 1300-årene - Kock, Jan (Hikuin, 2001)
The kilns from Barmer. Potter’s kilns from the 14th century By Jan Kock Two potter’s kilns were found near the village of Barmer, in western Himmerland. Both are the horizontal type of kiln, with the firing chamber placed in continuation of the fire chamber. The best-preserved kiln lay east-west, and was 3 m long and a little over 1 m wide. The entire bottom of the kiln was lined with a strong, sand-tempered clay mixture, carefully laid out and smoothed over. The kiln dome was also built of sand-tempered clay, and supported by a skeleton of branches that later burned off. The fire chamber lay to the west and was slightly sunken, about 30 cm lower than the oven chamber. The two sections were separated by three heavy pillars of clay. The firing chamber rose slightly toward the opening, which was preserved at the east end of the kiln. A considerable amount of pottery was found in and around the kiln, in general typical of the 14th century. C-14-dating places the kiln in the second half of the 14th century. See the article on the pottery from Barmer in this publication.